THE PROCESSING OFKWETIAUMADE FROM THE SNAKEHEAD FISH PROTEIN CONCENTRATE (Channa striatus) FORTIFIED WITH KARAGENAN - Sinaga, Sanni Ezra; Dewita, Dewita; Desmelati, Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThe research aimed to determine the effect of addition of flour carrageenan at different concentrations on the quality ofkwetiaumade from the snakehead fish protein concentrate. The research used an experimental method andcomposedas a non-factorial Completely Randomized Design (CRD). The treatment conducted wasaddition of carrageenan flour varied in 4 concentrations (0, 2, 6, and 10 %). The results showed that the addition of carrageenan flour was affecting significantly to the snakehead fish protein concentrate kwetiauproduced that wasevaluated by the different sensory value of the taste, aroma, and texture value; folding test, moisture content, protein content, and ash content; and elongation value. The best kwetiau produced was indicated by the addition of carrageenan flour at aconcentration of 2%. This product was characterized by the higestvalue of appearance on7.3 (whole, slightly brownish white), aroma on 6.4 (a little seaweed aroma), taste on 6.7 (slightly tasted seaweed), and textureon 7.7 (chewy and soft). The value of folding test was 8.0 (not cracked when folded one) and the elongation value was 26.48. The content of ash was 2.20 %, protein was 18.68 %, and waterwas 68.11%. Keywords: Carrageenan,kwetiau,rice flour, snakehead fish,snakehead fish protein concentrate,